2020
DOI: 10.1080/13683500.2020.1803807
|View full text |Cite
|
Sign up to set email alerts
|

Travel risk perception and travel behaviour during the COVID-19 pandemic 2020: a case study of the DACH region

Abstract: The study examined the relationship between perception of COVID-19, travel risk perception and travel behaviour among travellers in the DACH region (Germany, Austria, Switzerland)an important tourism market and, after Italy, the second region in Europe that was impacted by COVID-19. Data were collected at two points of time: the sample of the study in Period 1 (n = 1158) was collected at a critical point in time in the beginning of March 2020, when Italy was already massively affected by COVID-19; the sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
374
4
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 502 publications
(506 citation statements)
references
References 40 publications
27
374
4
17
Order By: Relevance
“…Senbeto and Hon (2020) have stated that major health crises, such as 2003 SARS and 2015 avian flu outbreaks, seem to impact tourist behaviour more than a financial crisis, bringing anxiety and influencing travel intentions regardless of tourists' profile. Recent studies addressing the COVID-19 pandemic (Nazneen, Hong & Ud Din, 2020;Neuburger & Egger, 2020) have confirmed the previous ones and showed that tourist health risk perception has increased, affecting negatively individuals' travel intentions.…”
Section: Tourism and Risk Perceptionmentioning
confidence: 54%
See 4 more Smart Citations
“…Senbeto and Hon (2020) have stated that major health crises, such as 2003 SARS and 2015 avian flu outbreaks, seem to impact tourist behaviour more than a financial crisis, bringing anxiety and influencing travel intentions regardless of tourists' profile. Recent studies addressing the COVID-19 pandemic (Nazneen, Hong & Ud Din, 2020;Neuburger & Egger, 2020) have confirmed the previous ones and showed that tourist health risk perception has increased, affecting negatively individuals' travel intentions.…”
Section: Tourism and Risk Perceptionmentioning
confidence: 54%
“…Previous studies revealed that perceived tourism risk may decrease re(visit) intention in case of natural disasters (Lehto, Douglas & Park, 2008;Chew & Jahari, 2014;Rittichainuwat, Nelson, & Rahmafitria, 2018), terrorism (Sönmez & Graefe, 1998;Floyd et al, 2004;Adeloye & Brown, 2017), and diseases (Mizrachi & Fuchs, 2016;Novelli et al 2018;Neuburger & Egger, 2020;Nazneen, Hong & Ud Din, 2020).…”
Section: Tourism and Risk Perceptionmentioning
confidence: 99%
See 3 more Smart Citations